2018
DOI: 10.3390/f9060298
|View full text |Cite
|
Sign up to set email alerts
|

Wood and Fiber Quality of Plantation-Grown Conifers: A Summary of Research with an Emphasis on Loblolly and Radiata Pine

Abstract: Abstract:With conifer plantations having an increasingly important role in meeting the fiber needs of society, an understanding of the effect of silvicultural practices on wood quality is critical. The perception of wood quality varies, making it hard to define in a single statement; however, possibly the most succinct definition is "a measure of the aptness of wood for a given use". In general, properties that have a positive influence on a specific product assist in defining changes in wood quality. Since wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 69 publications
0
16
1
2
Order By: Relevance
“…Understanding of mechanisms and dynamics of wood formation in boreal regions progressed quickly during the last 20 years. A lot of literature is available on wood formation, anatomical traits and quality (Rossi et al 2006, Cuny & Rathgeber 2016, Schimleck et al 2018. However, there is still limited effort being made to explore the mechanisms and quantify the relationships between wood quality and cell anatomical traits.…”
Section: Perspectives For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding of mechanisms and dynamics of wood formation in boreal regions progressed quickly during the last 20 years. A lot of literature is available on wood formation, anatomical traits and quality (Rossi et al 2006, Cuny & Rathgeber 2016, Schimleck et al 2018. However, there is still limited effort being made to explore the mechanisms and quantify the relationships between wood quality and cell anatomical traits.…”
Section: Perspectives For Future Researchmentioning
confidence: 99%
“…Wood market demands and forest industries require a better understanding of basic wood properties such as juvenile and mature wood, average density, earlywood and latewood proportion, fiber/tracheid length and microfibril angle. The study of the response of these traits to climate change is often neglected because the emphasis is on quantity and quality improvement of trees through management and breeding practices (Hart 2010, Schimleck et al 2018. Many studies focus on tree genetics and wood traits (Beaulieu et al 2011, Resende et al 2012, because wood properties are partly controlled by genetics (Lenz et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies in conifer species have reported effects of plantation density on growth (diameter and slenderness) and wood and fiber properties. Wider spacing at planting has been reported to be associated with higher tree diameter and lower MOE in Scots pine (Persson et al, 1995) and a number of coniferous species (Chuang and Wang, 2001;Zhang et al, 2002;Clark et al, 2008;Lasserre et al, 2008Lasserre et al, , 2009Schimleck et al, 2018). Ring width and wood density are negatively correlated, and MOE negatively correlated with wood density and MFA, respectively (Loo et al, 1984;Hodge and Purnell, 1993;Zhang and Morgenstern, 1995;Waghorn et al, 2007;Gaspar et al, 2008;Lasserre et al, 2009;Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical and physical properties of wood are important factors used to determine the suitability and application of wood material (Babiak et al 2018). Wood basic density is defined as the ratio of dry matter content to green volume of a sample and is the most widely used indicator of wood quality (Schimleck et al 2018). The wood basic density is easy to measure and has an important influence on the evaluation of wood properties, not only on the mechanical strength of wood, but also on the genetic improvement of wood.…”
Section: Introductionmentioning
confidence: 99%